PERANCANGAN VIDEO PROMOSI DESTINASI WISATA BAHARI DI PASAMAN BARAT - Salsabilla Hafiza (IAM Indonesia, 2023)
Abstract West Pasaman Regency is one of the results of the expansion of West Sumatra with the capital city of Simpang 4. It is known as the largest producer of palm oil in West Sumatra. West Pasaman Regency has several marine tourism that are so beautiful, safe, and still well maintained that are quite competitive with other tours. These marine tourism include Sasak Beach, Maligi Beach, Sikilang Beach, Sikabau Beach, Air Bangis Beach, Panjang Island and Pigago Island. However, there are still many tourists outside the West Pasaman area who still don't know about marine tourism in West Pasaman, because the introduction media on social media have not provided the maximum. In order to maximize efforts to introduce marine tourism in Pasaman, a promotional video will be designed which aims to introduce marine tourism in West Pasaman so that it is better known, known, and attracts tourists outside the West Pasaman area and the public to visit marine tourism in West Pasaman. The introduction of marine tourism will be more maximal later and with this promotional video, it can maximize the use of social media by the people of West Pasaman. Keywords: Promotional video, Marine Tourism, West Pasaman Sea